Factors And Conditions of Recognition of People with Diabetes Using Alternative Health Care (AHC) In Sambas, Indonesia - Parliani, Parliani; Pearkao, Chatkhane (Journal of Neonatal Surgery, 2025)
Background: Alternative Health Care (AHC) is one of medication that famous among Indonesian. One of ethnic that have high cultural belief is Malay who have their own unique concoction and decoction for solve their disease. Understanding factors and condition using AHC among Malay culture can be one of deeply exploring for develop nursing cultural care. Purpose: The aims of study is to explore and understand the factors and conditions using AHC among people living with diabetes in Kalimantan Barat Methods: The method of study is qualitative study using ethnography study to explore universe of factors and conditions using AHC among persons living with diabetes. The setting is in Sambas, Kalimantan Barat with total respondents in this study are 45 respondents. They are diabetes people, their families, health care providers, health care volunteers and community leaders. Results: The results of this study are first, internal factors such as feeling comfortable, motivations to be healthy, effectiveness of AHC, knowledge of AHC, respect to old people and respect to culture, second, social and community factors such as social belief, community support, information from society, and social practice. Third, economy and accessibility factors such as ready in community, easy to get, cheap and traditional healer can come to house. Conclusion: For culture underpinning, collaboration between traditional and professional health care provider should be improved to find holistic view of diabetes people management, to see the impact of each medication treatment that the persons with diabetes do. Moreover, this study also found in some special case that if the body feel good means there is no body problem condition although they live with diabetes, but if the body feel uncomfortable means should be gotten treatment because it influences their all life such as their work, their stress and their community activities.